Computational insights in CD58 binding to ASFV CD2v and in silico optimization of nanobody designs against the interface - Albert Neil Gura Dulay; Richelle Mae Evasco Padilla; Nyzar Mabeth Obenio Odchimar; Fredmoore Legaspi Orosco (Open Veterinary Journal)
Background: African swine fever (ASF) continues to hamper pork production worldwide. In addition to vaccines, there is a need to develop curative therapeutics, such as highly-specific antibodies or nanobodies, against immunogenic proteins with important functions such as the viral CD2-like protein (CD2v). However, further characterization of CD2v, such as its binding with cellular partners, is needed for the rational development of such biologics.